(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2013)
Introduction. The concept of sensitivity in Electrical Impedance Tomography is introduced (first – fourth type). The experimental researches measuring the voltages on the phantom outline are conducted on the created layout (for uniform cylindrical vessel with brine and placed inhomogeneities in a vessel). The main part. The inverse problems are solved for simulated on PC phantom (the third type sensitivity) and from measured results (the fourth type sensitivity) by conductivity zones method using regularization by A. Tykhonov. The sensitivity to conductivity increasing of elements inside the phantom is significantly less than the sensitivity to resistance increasing. The results of measured voltages processing and the results of projection reconstruction (obtained from mathematical model and from measured results) are described. Conclusions. The satisfactory agreements of reconstruction results between themselves and with mathematical and measured phantoms are shown.